2021
DOI: 10.1055/s-0041-1725205
|View full text |Cite
|
Sign up to set email alerts
|

CT-guided Thoracic Sympathicolysis versus VATS Sympathectomy in the Therapeutic Concept for Severe Primary Palmar Hyperhidrosis

Abstract: Background The objective was to compare computed tomography (CT)-guided thoracic sympathicolysis (CTSy) and video-assisted thoracoscopic sympathectomy (VATS) with regard to their feasibility, the occurrence of minor and major complications, and the clinical outcome. Materials and Methods In this study, 88 patients treated by CTSy and 86 patients treated by VATS were retrospectively included. CTSy was performed after establishing the entry plane below the level of the intervertebral space T2/3 via a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…Resen et al conducted a study on the effectiveness of CT-guided chemical destruction of the thoracic sympathetic nerve chain with absolute alcohol in treating palmar hyperhidrosis. The study included 86 cases and the results showed that the short-term curative effect was observed to be 100% ( 27 ), and the curative effect is comparable to ETS within one year but with fewer complications ( 28 ). However, although absolute alcohol chemical damage block has high immediate efficiency, the time effect is far less lasting than ETS, with a 3 year recurrence rate as high as 68.75% and a 55.88% incidence of postoperative compensatory hyperhidrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Resen et al conducted a study on the effectiveness of CT-guided chemical destruction of the thoracic sympathetic nerve chain with absolute alcohol in treating palmar hyperhidrosis. The study included 86 cases and the results showed that the short-term curative effect was observed to be 100% ( 27 ), and the curative effect is comparable to ETS within one year but with fewer complications ( 28 ). However, although absolute alcohol chemical damage block has high immediate efficiency, the time effect is far less lasting than ETS, with a 3 year recurrence rate as high as 68.75% and a 55.88% incidence of postoperative compensatory hyperhidrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Kuijpers et al, [1] using a bilateral one-stage single-port sympathectomy procedure, reported not only a significant reduction in HDSS scores but also severe compensatory hyperhidrosis with a frequency ranging between 17.1% and 32.8% of patients. In a comparative study, Andresen et al [31] compared CTguided thoracic sympathicolysis and video-assisted thoracoscopic sympathectomy for PPH and found both treatments resulted in a marked reduction of symptoms, but transient compensatory sweating was reported in 14.9% of cases after both approaches, and videoassisted thoracoscopic sympathectomy resulted in postoperative pneumothorax in 8% and temporary thoracotomy pain in 14% of patients. In another comparative study of T3 thoracoscopic sympathectomy versus T3+T4 sympathectomy, Yang et al [32] found that both techniques resulted in a significant reduction of a sweating index, but they also resulted in compensatory hyperhidrosis with an incidence of 5-10%, with the possibility of postoperative neuralgia and pneumothorax requiring chest tube placement.…”
Section: Discussionmentioning
confidence: 99%